Validation of a device for the active manipulation of the tumor microenvironment during intravital imaging. Issue 2 (3rd May 2016) - Williams, James K.; Entenberg, David; Wang, Yarong; Avivar-Valderas, Alvaro; Padgen, Michael; Clark, Ashley; Aguirre-Ghiso, Julio A.; Castracane, James; Condeelis, John S.
ABSTRACT: The tumor microenvironment is recognized as playing a significant role in the behavior of tumor cells and their progression to metastasis. However, tools to manipulate the tumor microenvironment directly, and image the consequences of this manipulation with single cell resolution in real time in vivo, are lacking. We describe here a method for the direct, local manipulation of microenvironmental parameters through the use of an implantable Induction Nano Intravital Device (iNANIVID) and simultaneous in vivo visualization of the results at single-cell resolution. As a proof of concept, we deliver both a sustained dose of EGF to tumor cells while intravital imaging their chemotactic response as well as locally induce hypoxia in defined microenvironments in solid tumors.